PENGELOLAAN KELAS GURU GEOGRAFI DI SMA NEGERI 1 BANJIT TAHUN PELAJARAN 2014/2015 - Emtizal Saprodi; Yarmaidi Yarmaidi; Rosana Rosana (JPG (Jurnal Penelitian Geografi), 2015)
The objective of this research was to determine classroom management by geography teachers at SMAN 1 Banjit in academic year 2014/2015. The method was descriptive method. The population was all students of class X. The data collection techniques were interviews, questionnaires, observation and documentation. The data analysis used was descriptive analysis. Based on the research, it showed 1. The motivation for learners was good enough (42.5%) and (42.5%) 2. The methods and learning models were good enough (31.25%) 3. The order of learning materials was good enough (46.25%) 4. The setting for an effective exercise was good enough 43.75%, (37.5%) and (41.25%) 5. The issue of individual differences of learners was good (55%) 6. The evaluation of the learning was good enough (47.5 %) (36.25%) and (40%) The directions for the students were good enough (35%) and (57.5%) 7. The infrastructures were good enough (38.75%) and (27.5%).Penelitian ini bertujuan untuk mengetahui pengelolaan kelas guru mata pelajaran geografi di SMA Negeri 1 Banjit Tahun Pelajaran 2014/2015.Metode penelitian adalah deskriptif. Populasi adalah seluruh siswa kelas X. Teknik pengumpulan data adalah wawancara, kuesioner, observasi dan dokumentasi. Analisis data menggunakan analisis deskriptif. Berdasarkan hasil penelitian menunjukkan 1. Motivasi kepada peserta didik cukup baik (42,5%) dan (42,5%) 2. Penggunaan metode dan model pembelajaran sudah cukup baik (31,25%) 3. Urutan materi pembelajaran sudah cukup baik (46,25%) 4. Pengaturan latihan yang efektif sudah cukup baik 43,75%, (37,5%) dan(41,25%) 5. Masalah perbedaan individu peserta didik sudah baik (55%)6. Evaluasi pembelajaran sudah cukup baik (47, 5%) (36,25%) dan (40%) bimbingan siswa sudah cukup baik (35%) dan (57,5%) 7. Sarana dan Prasarana sudah cukup baik (38,75%) dan (27,5%).Kata kunci: pengelolaan kelas, guru geografi, pembelajaran